Central circuits in control of energy expenditure: connecting energy and temperature homeostasis - Clint Kinney; Laura Kaiser; Christopher D. Morrison; Hans-Rudolf Berthoud; Heike Münzberg (Journal of Comparative Physiology B, 2026)
Energy expenditure (EE) is the dynamic physiological process that balances energy intake to maintain body weight and body temperature. Environmental changes induce EE adaptations that limit fluctuations in body weight or body temperature by balancing between body temperature defense and energy conservation. The central nervous system (CNS) orchestrates these adaptations by integrating multiple external and internal cues to coordinate thermogenesis together with other behavioral and metabolic processes. Key hypothalamic and brainstem nuclei form a distributed network that modulates autonomic output to peripheral organs, including sympathetic tone to brown and white adipose tissues. Here, we review known neural circuits and neurotransmitter systems, their integration with sensory pathways and functionally opposing output discrepancies that reveal knowledge gaps how the CNS switches between body temperature defense and energy preservation.

Orexin inputs to caudal raphé neurons involved in thermal, cardiovascular, and gastrointestinal regulation - Hans-Rudolf Berthoud; Laurel M. Patterson; Gregory M. Sutton; Christopher Morrison; Huiyuan Zheng (Histochemistry and Cell Biology, 2005)

Vanilloid receptor (VR1) expression in vagal afferent neurons innervating the gastrointestinal tract - Laurel M. Patterson; Huiyuan Zheng; Sean M. Ward; Hans-Rudolf Berthoud (Cell and Tissue Research, 2003)

Immunohistochemical identification of cholecystokinin A receptors on interstitial cells of Cajal, smooth muscle, and enteric neurons in rat pylorus - Laurel M. Patterson; Huiyuan Zheng; Sean M. Ward; Hans-Rudolf Berthoud (Cell and Tissue Research, 2001)